P-T-T history of the Amasia and Stepanavan sub-ophiolitic metamorphic units (NW Armenia, Lesser Caucasus): implications for metamorphic sole development and for the obduction process - Hässig, Marc; Rolland, Yann; Melis, Raphael; Sosson, Marc; Galoyan, Ghazar; Bruguier, Olivier (Ofioliti, 2019)
The Sevan-Akera suture zone ophiolites are relics of a vast ophiolitic nappe which testifies a major obduction event, up to 300 km of horizontal transport, of the northern branch of Neotethys oceanic crust over the South Armenian/Taurides continental block. Near the locality of Amasia (NW Armenia), garnet-bearing amphibolites are preserved within a greenschist facies tectonic mélange unit located below the non-metamorphic obducted oceanic unit. The garnet amphibolites show two parageneses: (1) garnet-amphibole-plagioclase granoblasts which crystallized along the S1 foliation intensely folded and recrystallized into (2) epidote-chlorite-phengite during retrogression and S2deformation. S1 and S2 deformation stages feature top-to-the-South ductile shearing, interpreted as the motion of the ophiolite nappe during obduction. Thermobarometry reveals a metamorphic history with two P-T fields: (1) an amphibolite stage, T = 600±20°C and 6 ≤P ≤7 kbar,followed by (2) a greenschiststage, T = 350±30°C and 1.25 ≤P ≤4.5 kbar. 40Ar/39Ar dating on amphiboles and white micas yields similar within-error ages of 88-92±2 Ma. U-Pb dating on rutile yields an age of 90.2±5.2 Ma. These results are complemented by new and pre-existing characterizations of lithologies in a similar structural position 40 km east, in the locality of Stepanavan. There, newly identified eclogite yield metamorphic conditions of T = 575±25°C and 17.5 ≤P ≤20 kbar.The P-T-t history of these metamorphic units argues for a rapid tectonic process featuring intra-oceanic subduction below a relatively hot oceanic lithosphere, slicing of the overriding oceanic domain, underplating of this subducted material along the hanging wall of the subduction zone and formation of a metamorphic sole as part of an ‘obduction channel’.